Analysis of Communication Patterns at Pengharapan Baptist Church in Surabaya on Implementing Simple Church - Imanuela Winda Putri; Dimas Satrio Wijaksono (Publikasi Indonesia, 2024)
This study aims to analyze the communication patterns at GBI Pengharapan Surabaya in the implementation of the Simple Church model. Effective communication is a key element in supporting structural and operational changes within the church organization. This research uses a qualitative approach with data collection techniques through in- depth interviews with three informants: one expert informant, one key informant, and one supporting informant. The expert informant is the senior pastor of Hope Baptist Church, who has extensive experience in leading various organizations. He is the person who introduced and taught the Simple Church concept at GBI Pengharapan Surabaya. The key informant is the assistant pastor of GBI Pengharapan Surabaya, who plays a significant role in directing and implementing the Simple Church model in the church. The supporting informant is an active congregation member who provides perspective on the experiences and impacts of communication changes in the daily life of the church. The results of the study indicate that downward communication, upward communication, and lateral communication at GBI Pengharapan Surabaya function well, with information and instructions flowing effectively from the senior pastor and leadership to the congregation and vice versa through various channels. Furthermore, lateral communication among church committees demonstrates strong synergy and effective coordination. The findings also show that the church’s communication network employs various patterns that support effective interaction, such as the chain pattern for sequential information flow, the wheel pattern with a clear central information hub, the circle pattern allowing cyclical communication among group members, the free-flow pattern enabling communication unrestricted by formal hierarchy, and the Y pattern connecting information through two main channels to a central point. All these patterns are well-implemented, supporting operational efficiency and collaboration within the church.